Plant Parasitic nematodes associated with Maple (Acer caesium) and Poplar (populous nigra) in district Swabi - Bilal Muhammad; Mian Sayed Khan; Saira Saira (RADS Journal of Biological Research & Applied Science, 2023)
Background: Parasitic nematodes are very destructive to crops, ornamental plants and woody plants as well which cause most severe diseases in plants and feed on the roots of these plants.